Portal lymphadenopathy associated with lipofuscin in chronic cholestatic liver disease. Issue 11 (November 1989) - Hübscher, S G; Harrison, R F
Abstract : To determine whether portal lymphadenopathy in primary biliary cirrhosis is caused by deposition of lipofuscin pigment in sinus histiocytes and to compare primary biliary cirrhosis with other liver diseases a retrospective study on a consecutive series of 169 livers obtained at transplantation was carried out. There were grouped into eight diagnostic categories: primary biliary cirrhosis (n = 51), primary sclerosing cholangitis (n = 10), extrahepatic biliary atresia (n = 6), chronic rejection (n = 9), cirrhosis (other causes) (n = 38), primary liver neoplasia (n = 21), acute liver disease (n = 20), and retransplantation (other) (n = 14). Lymph nodes were present in 66 specimens. Fifty of these contained granules of lipofuscin pigment. The highest incidence of lymph node enlargement and the largest amounts of pigment were present in cases of primary biliary cirrhosis. A similar pattern of lymph node enlargement was also commonly observed in other chronic cholestatic conditions (primary sclerosing cholangitis, biliary atresia, chronic rejection). Much less pigment was seen in nodes draining livers with non-cholestatic cirrhosis or primary tumours. Nodes were not found in acute liver disease. It is concluded that portal lymphadenopathy associated with lipofuscin is a common finding in various chronic cholestatic liver diseases. The pathogenesis of this lesion is uncertain. Most cases are asymptomatic with enlarged nodes which may be detected only at laperotomy or necropsy and may be wrongly attributed to neoplastic disease. Diagnostically, the finding of large amounts of lipofuscin in enlarged portal lymph nodes is a good indicator of underlying chronic cholestatic liver disease.